Real-Time Order Monitoring: Transforming E-Commerce Operations - Santosh Nakirikanti, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Real-time order monitoring represents a transformative advancement in e-commerce operations, enabling businesses to track, analyze, and optimize the entire fulfillment process as events occur. This technological evolution has shifted the industry from retrospective batch processing to instantaneous event-driven architectures that capture each customer interaction as it happens. Through specialized components including event producers, message brokers, stream processors, and real-time databases, these monitoring systems deliver unprecedented visibility across the order lifecycle. The integration of advanced analytics further enhances these capabilities, enabling predictive insights and automated responses that address issues before they impact customer experience. Despite technical challenges related to scalability, data consistency, and latency management, innovative solutions have emerged to ensure reliable operation at scale. As these systems mature, emerging technologies such as artificial intelligence, Internet of Things, blockchain, and immersive visualization are extending monitoring capabilities beyond passive observation toward active orchestration of the entire customer journey.
Keywords: Blockchain; E-Commerce; Event-Driven Architecture; Real-Time Monitoring; Stream Processing